2020
DOI: 10.1075/sll.19014.hud
|View full text |Cite
|
Sign up to set email alerts
|

Negation and polar question–answer clauses in South African Sign Language

Abstract: This paper contributes to the typological debate of whether sign languages should be divided into manual versus non-manual dominant languages, w.r.t. negation, a distinction that has recently been challenged (Johnston 2018) or argued to be too radical (Oomen & Pfau 2017), by providing a characterization of negation in South African Sign Language (SASL). It has also been observed in several sign languages that a construction which consists of a yes-no question followed by a negative fragment answer, both pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 35 publications
0
1
0
Order By: Relevance
“…A review of the literature has shown many studies that investigates polar (yes/no) questions) in many languages and some issues related to them such as English negative polar questions (Aksenovová, 2022); negative polar question types in English (Romero, Arnhold, Braun & Domaneschi, 2017); negative polar questions in English and Czech (Malá, 2007); polar questions in Seri (Marlett & Moser, 2000); negation, alternatives, and negative polar questions in American English (AnderBois, 2019); negative answers to polar questions in English (Park & Yang, 2022); (Dis) agreement, polarity, and focus in answers to negative polar questions in Italian (Servidio, Bocci & Bianchi, 2018); polar question forms expressing bias-evidence conflicts in Italian (Di Maro, Origlia, & Cutugno, 2021); the particle mica in Italian polar questions and attitudes in discourse (Frana, & Rawlins, 2019); affirming responses to polar questions in Russian conversation (Bolden, 2016); question bias and question concern in negative polar questions in Russian (Repp & Geist, 2022); the syntax of answers to polar questions in English and Swedish (Holmberg, 2013); new perspectives on bias in polar questions in Hungarian (Gyuris, 2017); what is and (isn't) asked with a (negative) polar question in Serbian? (Todorovic, 2022); intonation and its interfaces in Sardinian polar questions (del Mar Vanrell, Ballone, Schirru, & Prieto, 2014); the interpretation of responses to particles méi (yǒu) and bù in negative polar questions in Mandarin Chinese (Li, Borràs-Comes & Espinal, 2022); the syntax of polar questions and their answers in Taiwanese (Wu, 2016); embedded negative polar questions in Japanese (Goodhue & Shimoyama, 2022); two varieties of negative polar interrogatives in Japanese (Ito & Oshima, 2014); bias and prosody in Japanese negative polar questions (Ito, 2015); the anaphoric nature of particle responses to the polar questions in English and Korean (Kim, 2017); variations in answering negative polar questions in Korean (Kim, Nam & Kim, 2023); negation and polar question-answer clauses in South African sign language (Huddlestone, 2021); what negative polar questions can teach us about the in domain for Turkish sign language (Gokgoz, 2010); negative polar questions in Hong Kong sign language (Sze & Lee, 2022) and others.…”
Section: Introductionmentioning
confidence: 99%
“…A review of the literature has shown many studies that investigates polar (yes/no) questions) in many languages and some issues related to them such as English negative polar questions (Aksenovová, 2022); negative polar question types in English (Romero, Arnhold, Braun & Domaneschi, 2017); negative polar questions in English and Czech (Malá, 2007); polar questions in Seri (Marlett & Moser, 2000); negation, alternatives, and negative polar questions in American English (AnderBois, 2019); negative answers to polar questions in English (Park & Yang, 2022); (Dis) agreement, polarity, and focus in answers to negative polar questions in Italian (Servidio, Bocci & Bianchi, 2018); polar question forms expressing bias-evidence conflicts in Italian (Di Maro, Origlia, & Cutugno, 2021); the particle mica in Italian polar questions and attitudes in discourse (Frana, & Rawlins, 2019); affirming responses to polar questions in Russian conversation (Bolden, 2016); question bias and question concern in negative polar questions in Russian (Repp & Geist, 2022); the syntax of answers to polar questions in English and Swedish (Holmberg, 2013); new perspectives on bias in polar questions in Hungarian (Gyuris, 2017); what is and (isn't) asked with a (negative) polar question in Serbian? (Todorovic, 2022); intonation and its interfaces in Sardinian polar questions (del Mar Vanrell, Ballone, Schirru, & Prieto, 2014); the interpretation of responses to particles méi (yǒu) and bù in negative polar questions in Mandarin Chinese (Li, Borràs-Comes & Espinal, 2022); the syntax of polar questions and their answers in Taiwanese (Wu, 2016); embedded negative polar questions in Japanese (Goodhue & Shimoyama, 2022); two varieties of negative polar interrogatives in Japanese (Ito & Oshima, 2014); bias and prosody in Japanese negative polar questions (Ito, 2015); the anaphoric nature of particle responses to the polar questions in English and Korean (Kim, 2017); variations in answering negative polar questions in Korean (Kim, Nam & Kim, 2023); negation and polar question-answer clauses in South African sign language (Huddlestone, 2021); what negative polar questions can teach us about the in domain for Turkish sign language (Gokgoz, 2010); negative polar questions in Hong Kong sign language (Sze & Lee, 2022) and others.…”
Section: Introductionmentioning
confidence: 99%